English Textbook Evaluation for 8th Grade of Junior High School Based on Thomlinson’s Theory - fitri Handayani; mike amelia (English Language Education Department, Universitas Majalengka, 2023)
This study conducts a comprehensive evaluation of English textbooks designed for 8th-grade students in junior high schools, utilizing Thomlinson's Theory of Differentiation as the theoretical framework. The objective is to assess the alignment of these textbooks with Thomlinson's principles of differentiated instruction, which emphasize tailoring educational materials to cater to the diverse learning needs of students. This study is part of an evaluation study, incorporating qualitative content analysis and quantitative assessment to gauge the textbooks' suitability for enhancing student engagement and learning outcomes. Findings from this evaluation will inform educators and curriculum developers about the extent to which these textbooks effectively address the requirements of 8th-grade English learners, with implications for improving teaching and learning strategies in the junior high school context.